Local employment growth in West Germany: a dynamic panel approach - Uwe Blien; Jens Suedekum; Katja Wolf (Institute for the Study of Labor (IZA), 2005)
In this paper we study the dynamics of local employment growth in West Germany from 1980 to 2001. Using dynamic panel techniques, we analyse the timing of the impact of diversity and specialisation, as well as of the human capital structure of local industries. Diversity has a positive effect on employment growth in the short run, which is stronger in manufacturing than in services. Concerning specialization we find evidence for mean reversion, which is inconsistent with the idea that growth emphasizes itself. But there is considerable inertia in this process. A positive effect of education is only found in manufacturing. Additionally, we look at the impact of firm size and regional wages on local employment growth.
Keywords: R11; O40; 330; regional labor markets; externalities; local employment growth; dynamic panel estimation; urbanization and localisation effects; Regionaler Arbeitsmarkt; Regionales Wachstum; Beschäftigungseffekt; Lokalisationseffekt; Regionale Wirtschaftsstruktur; Wissenstransfer; Schätzung; Deutschland; Urbanisierungseffekt